Advancing detection and response capacities for emerging and re-emerging pathogens in Africa - Nachega, Jean B; Nsanzimana, Sabin; Rawat, Angeli; Wilson, Lindsay A; Rosenthal, Philip J; Siedner, Mark J; Varma, Jay K; Kilmarx, Peter H; Mutesa, Leon; Tanner, Marcel; Binagwaho, Agnes; Forrest, Jamie; et al. (The Lancet Infectious Diseases, 2023)
Recurrent disease outbreaks caused by a range of emerging and resurging pathogens over the past decade reveal major gaps in public health preparedness, detection, and response systems in Africa. Underlying causes of recurrent disease outbreaks include inadequacies in the detection of new infectious disease outbreaks in the community, in rapid pathogen identification, and in proactive surveillance systems. In sub-Saharan Africa, where 70% of zoonotic outbreaks occur, there remains the perennial risk of outbreaks of new or re-emerging pathogens for which no vaccines or treatments are available. As the Ebola virus disease, COVID-19, and mpox (formerly known as monkeypox) outbreaks highlight, a major paradigm shift is required to establish an effective infrastructure and common frameworks for preparedness and to prompt national and regional public health responses to mitigate the effects of future pandemics in Africa.
Keywords: Pathogens; Disease outbreak; Public health preparedness; Detection; Africa